O Livro I de Diógenes Laércio: a tradição dos Sete Sábios e a caracterização da figura do sophos - Leão, Delfim (2013)
The first part of the study is devoted to the weight carried by Plato in the making of the tradition of the Seven Wise Men. In the second part, an approach is made to that same tradition in Diogenes Laertius, thereby in a stage when the main lines concerning the characterization of those personalities were already stabilized. The results of this process of crystallization are discussed taking as reference the way Diogenes depicts one of the most paradigmatic personalities of the group of sophoi: the Athenian legislator Solon.